Tropical tree monocultures: \"green deserts\" or \"nurse trees\" fostering forest succession? - Simões, Laura Helena Porcari (2024)
A large proportion of tree plantations in the tropics are monocultures of exotic species. In addition to their well-established role in supplying timber products to the industry, tree monocultures have been used to stimulate the natural regeneration of native species, which has generated controversy. Although the area planted with tree monocultures is still increasing in the tropics, there are also many plantations that have had their management practices interrupted for legal, financial and/or operational reasons. The objective of this study is to understand to what extent unmanaged tree monocultures can contribute to the restoration of forest landscapes by promoting the structural complexity, diversity and functionality of native tree species. To achieve this objective, this thesis was divided into three chapters. In the first chapter, we reviewed the global literature to assess the regeneration potential of woody species in understories of tropical tree monocultures, including a case study from Brazil. The second and third chapters were based on primary data collected throughout the state of São Paulo, Brazil. In the second chapter, we assessed how the diversity and structure of regenerating native woody species differ in unmanaged eucalyptus plantations and secondary forests as a function of age and local, landscape, and climatic factors. In the third chapter, we assessed how stand age, canopy strata, macroclimate, and soil characteristics affect the functional composition of unmanaged eucalyptus plantations and secondary forests. The results of this thesis indicate that tree monocultures can harbor a substantial forest succession, although not comparable to forest remnants or secondary forests. Plantations with longer rotations, composed of native species, and located adjacent to forest remnants harbor more species. Stand age influences both the diversity and structural attributes of unmanaged eucalyptus plantations, as they tend to shelter greater diversity of native woody species over time. However, weather was less important for the functional composition of regenerating native woody species when considering the community weighted means in different canopy strata. Climatic factors were relevant for the diversity and functional composition of regenerating native species in eucalypt plantations and secondary forests, but were of little relevance for structural attributes. Combined with other restoration strategies, unmanaged tree monocultures can be important allies to increase landscape connectivity and resilience, in addition to potentially providing financial benefits.